Evaluation of deformation-based seismic performance of RECC frames based on IDA method. (15th May 2020) - Wu, Chang; Pan, Zuanfeng; Jin, Chenhua; Meng, Shaoping
Highlights: The feasibility of using RECC in seismic resistant structures was discussed. An IDA-based method was used to evaluate the seismic performance at different levels. RECC frames show superior deformation capacity than RC frames under earthquake. Using ECC in key regions can both improve the seismic performance and lower the cost. Abstract: Engineered Cementitious Composites (ECC) is a typical High Performance Fiber Reinforced Cement-based Composite (HPFRCC), which possesses the characteristics of ultra-high tensile ductility and energy dissipation capacity. One of the potential applications of ECC is to replace conventional concrete in the seismic resistant structures. However, to date, the investigation on seismic performance of ECC at the structural level is still limited. This paper aims at evaluating the seismic performance of RECC frame on the basis of Performance-based Seismic Design (PBSD) concept and discussing the feasibility and practicability of applying ECC in structures for improving the seismic performance. The non-linear behavior of ECC material was simulated especially considering the strain hardening behavior in tension. By using the Incremental Dynamic Analysis (IDA) method, three types of frames, consisting of a normal RC frame, a RECC frame and an RECC/RC composite frame, were analyzed to evaluate the structural dynamic behavior of the frames. Comparative studies on the deformation limit states at five levels of seismic performance for these three different types of frames validated that RECC frames have superior deformation capacity comparing to traditional RC frames under high intensity earthquake. Comparison results also indicated that rationally applying ECC in key region of the structures can not only improve the seismic performance and deformation capacity of structures but also control the construction cost.